Sleep duration and quality of Brazilian nursing staff who work in shifts - Rosângela Marion da Silva; Regina Célia Gollner Zeitoune; Flávia Camef Dorneles Lenz; Carolina Renz Pretto; Katerine Moraes dos Santos; Tânia Solange Bosi de Souza Magnago; Alexa Pupiara Flores Coelho Centenaro (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objective: to analyze sleep duration and sleep quality in nursing professionals who work in shifts. Method: this is a cross-sectional, analytical research, carried out between September 2017 and April 2018, at a public hospital in southern Brazil, with the nursing team. A socio-occupational and health symptoms questionnaire, the Epworth Sleepiness Scale, and the Pittsburgh Sleep Quality Index were used. Data are presented as descriptive and inferential statistics, bivariate analysis, and binary logistic regression. Results: participants were 308 nursing professionals with a predominance of long-term sleep, absence of drowsiness, and poor sleep quality. Short-term sleep (<6h) was associated with day shift and poor sleep quality. Sleep quality was associated with presence excessive daytime sleepiness and work day shift. Conclusion: work shift, insomnia and headache were the main factors related short-term sleep for nursing professionals. The results may justify the development of intervention research for workers' health.